Topology Control Optimization of Wireless Sensor Networks for IoT Applications - Brito, Jorge A. G. de; P. Junior, Jurair R. de; Henriques, Felipe da R.; Assis, Laura S. de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
An Internet of Things (IoT) environment usually is composed by sensor nodes connected to the Internet, which constitutes a Wireless Sensor Network (WSN). In this work, the Sensor Allocation Problem (SAP) for a WSN is addressed, which defines the position of sensor nodes according to their different operation modes while pursuing the optimization of network efficiency with respect to performance parameters. An optimization methodology based on a Genetic Algorithm is proposed, in order to solve the SAP. Case studies are performed in order to evaluate the efficiency of the proposed solution method.